Laser Formation of Periodic Micro- and Nanostructures on the Surface of Monocrystalline Silicon - Mohylyak, I. A.; Bonchyk, O. Yu.; Korniy, S. A.; Kiyak, S. G.; Popovych, D. I. (Physics and Chemistry of Solid State, 2020)
Experimental studies of the features of the formation of laser-induced periodic nanostructures on the surface of silicon wafers in the zones of action of second, millisecond and nanosecond laser pulses are conducted in the work. The results of microscopic investigations by optical and electron microscopes of periodic structures formed on surfaces with crystallographic orientation (111), (100) are presented. The obtained results can be used to optimize the laser pulse mode for controlled micro- nanostructuring of the semiconductor surface.